The place and role of religion in the processes of ethno-national identification - Fylypovyč, Ljudmyla Oleksandrivna (Ukrai͏̈ns'ke relihijeznavstvo, 1999)
The acquisition of Ukraine in 1991 independence has actualized the problem of national identification of its peoples. According to the Constitution, they were able to have a full-fledged ethno-cultural existence not only Ukrainian but also other ethnic groups living in Ukraine. It turned out that religion, besides language, education, consciousness, and custom of the ritual elements of national life, is important for the processes of ethno-determination (especially Tatar, Polish, Jewish, German, Greek, Bulgarian and some other peoples of Ukraine).